A protocol for efficient plantlet regeneration from leaf derived callus of lablab bean (Lablab purpureus var. lignosus (L) prain) - Thiruvengadam, Muthu; Jayabalan, Narayanasamypillai (Universiti Putra Malaysia Press, 2003)
An efficient shoot bud differentiation and multiple shoot induction from leaf derived callus of Lablab bean (Lablab purpureus var. lignosus) have been obtained. Callus induction and shoot multiplication at various frequencies were observed using different concentrations and combinations of auxins (IAA, 2, 4-D and NAA) and cytokinin (RAP). The highest frequency of callus induction was observed on MS medium containing 2, 4-D (3.0 mg/1) and RAP (0.5 mg/1). The green compact nodular calli occurred on NAA (3.0 mg/1) and BAP (0.5 mg/1). Highest percentage of shoot bud formation and multiplication was obtained from a combination of RAP (2.0 mg/1) and NAA (0.5 mg/1). The regenerated shoots were transferred to MS medium containing IBA (1.5 mg/1) for the induction of roots. Rooted plants were transferred to plastic cups and subsequently these were successfully transferred to fields.